Joseph Kam 1815-1833: Perannya dalam Pendidikan di Ambon - Belly Isayoga Kristyowidi (IAKN Ambon, 2021)
This article aims to explore the role of Joseph Kam in the development of education and Christianity for the natives in Ambon in 1815-1833. This paper refers to the historical writing method in order to describe and analyze every event in the dimensions of space and time, with the principles of historical research, the historical method has stages from heuristics, verification, interpretation to historiography. The presence and efforts made by Joseph Kamp in the Dutch East Indies in particular in Ambon have made a major contribution to the indigenous people's literacy. His persistence in imparting education is always accompanied by the mission of the Nederlandsch Zendeling Genootschap to spread the gospel of Jesus Christ among the indigenous people. In addition to providing formal education by providing reading, writing, and arithmetic education to his students, Joseph Kamp also provides non-formal education by providing opportunities for his students to gain hands-on experience on how to operate a printing press or become part of the crew Schooner. Joseph Kam's persistence and hard work in serving the indigenous people have made an imprint on the hearts of Maluku.AbstrakTulisan ini bertujuan untuk menkesplorasi peran Joseph Kam terhadap perkembangan pendidikan dan kekristenan bagi para pribumi di Ambon pada tahun 1815-1833. Tulisan ini mengacu pada metode penulisan sejarah guna menguraikan dan menganalisis setiap peristiwa dalam dimensi ruang dan waktu, dengan kaidah-kaidah penelitian sejarah, metode sejarah memiliki tahapan dari heuristik, verifikasi, intepretasi hingga historiografi. Kehadiran serta usaha yang dilakukan oleh Joseph Kamp di Hindia Belanda secara khusus di Ambon telah memberikan kontribusi besar kepada masyarakat pribumi agar melek huruf. Ketekunannya dalam menanamkan pendidikan selalu dibarengi dengan misi dari Nederlandsch Zendeling Genootschap untuk mewartakan Injil Yesus Kristus di tengah-tengah masyarakat pribumi. Selain memberikan pendidikan secara formal dengan memberikan pendidikan membaca, menulis serta berhitung kepada para siswanya, Joseph Kamp juga membekali dengan pendidikan nonformal yaitu dengan memberikan kesempatan bagi para peserta didiknya untuk memperoleh pengalaman secara langsung tentang bagaimana cara mengoperasikan mesin cetak maupun menjadi bagian dari awak kapal Schooner. Kegigihan serta kerja keras Joseph Kam dalam melayani masyarakat pribumi telah membekas di hati masyarakat Maluku